2016
DOI: 10.1080/17470919.2015.1131194
|View full text |Cite
|
Sign up to set email alerts
|

Task influences pattern discriminability for faces and bodies in ventral occipitotemporal cortex

Abstract: Our prior research showed that faces and bodies activate overlapping regions of the ventral occipitotemporal cortex (VOTC). However, faces and bodies were nonetheless discriminable in these same overlapping regions when their spatial patterns of activity were classified using multi-voxel pattern analysis. Here we investigated whether these spatial patterns and their time courses were influenced by different categorization tasks. Participants viewed pictures of faces or headless bodies depicting a happy or fear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In the EBA, the optimal weight of body patterns was lower than that of face patterns for happy expressions, but it was almost the same as that of face patterns for angry and fearful expressions. Faces and bodies are both familiar and salient in our daily life, and often convey some similar information, leading to many common points of processing even in affective neuroscience ( de Gelder et al, 2010 , 2015 ; Kim and McCarthy, 2016 ). Furthermore, unlike many studies using headless bodies, we employed bodies with blurred faces to avoid the confounder in which the headless bodies act as novel stimuli that attract more attention than normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the EBA, the optimal weight of body patterns was lower than that of face patterns for happy expressions, but it was almost the same as that of face patterns for angry and fearful expressions. Faces and bodies are both familiar and salient in our daily life, and often convey some similar information, leading to many common points of processing even in affective neuroscience ( de Gelder et al, 2010 , 2015 ; Kim and McCarthy, 2016 ). Furthermore, unlike many studies using headless bodies, we employed bodies with blurred faces to avoid the confounder in which the headless bodies act as novel stimuli that attract more attention than normal.…”
Section: Discussionmentioning
confidence: 99%
“…By examining whether the perception of bodies was whole- or part-based, one study suggested that the response of the EBA increased linearly with the amount of body-related information (e.g., finger, hand, arm, torso), but in a step-like manner in the FBA, suggesting that the EBA shared a selective role for body parts and the FBA for whole persons or larger body parts ( Taylor et al, 2007 ; Bracci et al, 2015 ). Furthermore, the FG, which includes the FFA and FBA, could represent the characteristics of the whole person ( Kim and McCarthy, 2016 ). One previous study found that the synthetic patterns which are modeled by a linear combination of face- and body-evoked response patterns could precisely approximate the whole person-evoked response patterns in the right FG, implying a part-based manner of representation ( Kaiser et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mixed findings in previous studies might also be caused by the use of real-life objects (Kim and McCarthy, 2016;Long & Kuhl, 2018;Harel et al, 2014;Bracci et al, 2017;Vaziri-Pashkam & Xu, 2017;Hebart et al, 2018). In daily life, we often perform multiple tasks on the same object simultaneously (e.g.…”
Section: Mvpa Studies Of Task Effect On Object Processingmentioning
confidence: 94%
“…In Bracci et al (2017), while analyses with the representational dissimilarity matrices (RDM) suggested a task effect in the ventral but not lateral occipitotemporal cortex, the correlation between the response patterns for objects remained similar regardless of whether the task was the same or different in both regions. Kim & McCarthy (2016) reported a task effect on decoding face versus body images in the occipitotemporal fusiform cortex, but this finding came with a counter-intuitive observation that the face-body decoding was less accurate when participants were performing a face-body discrimination task compared with an irrelevant emotion discrimination task. Jackson et al (2017) reported above-chance decoding in the lateral occipital complex (LOC) only when the task was relevant, although the difference in decoding performance between task-relevant and task-irrelevant conditions was not statistically significant.…”
Section: Mvpa Studies Of Task Effect On Object Processingmentioning
confidence: 98%
“…Particularly, the FBA is partially overlapped with the FFA, and some similarities have been found between the processing of bodies and faces (Minnebusch and Daum, 2009; de Gelder et al, 2010). Because the fusiform gyrus (FG) contains both FFA and FBA, this area is considered to represent the characteristics of the whole person (Kim and McCarthy, 2016). Studies in macaques and humans have found that the STS, which acted as a crucial node for processing of social information, exhibited sensitivity to both faces and bodies (Pinsk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%